(untitled) (Damascus University Journal of agriculture sciences, 2022)
Asparaginase produced by Bacillus licheniformis using submerged fermentation under optimized conditions was purified. The purification process included the following steps; precipitation of protein by 80% acetone followed by sephadex G-100 gel filtration column then separation on DEAE- Sepharose column chromatography .Folds of purification of asparaginase reached 283.86 fold with specific activity of 667.08 IU/ml.